АНАЛІЗ ВТРАТ ЕНЕРГІЇ В СИСТЕМІ ВІДБОРУ МАКСИМАЛЬНОЇ ПОТУЖНОСТІ СОНЯЧНОЇ БАТАРЕЇ - Ромашко , В.Я.; Вербицький, Є.В.; Киричик, Є.І. (Інститут електродинаміки НАН України, Київ, 2014)
Expedience of picking maximum probable power from renewable electrical energy sources are validated. Electrical supply systems structure, which consist of such sources are considered. On solar battery example input current pulsation influence of harmonized switch converter to amount energy given from it are analyzed. Necessary solar battery work point shifting in left side relatively maximum power point are substantiated. Recommendation chosen of pulsation input current switch converter are given. Additional loses influence to work point position are shown. References 4, figures 5.